2021
DOI: 10.1136/bcr-2021-245653
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor tyrosine kinase inhibitor targeted therapy: a potential cause of an acute aortic dissection lesser known to the emergency physician

Abstract: A 59-year-old Chinese male presented to the emergency department with acute onset epigastric pain. He had no cardiovascular risk factors and was only on targeted therapy, pazopanib, for newly diagnosed metastatic renal clear cell carcinoma. He was found to have a Stanford type B acute aortic dissection with moderately elevated systolic blood pressure of 150 mm Hg. Although not a listed side effect, various case reports have shown a potential association between the use of vascular endothelial growth factor tyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The VEGFR signaling pathway plays an important role in aortic smooth muscle cell proliferation and migration ( Wang et al, 2021 ). The use of VEGR tyrosine kinase inhibitors may be linked to the development of acute AD ( Oshima et al, 2017 ; Ting and Lo, 2021 ). Similarly, the Rap1 signaling pathway is associated with cell migration, polarization, and proliferation ( Cha et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The VEGFR signaling pathway plays an important role in aortic smooth muscle cell proliferation and migration ( Wang et al, 2021 ). The use of VEGR tyrosine kinase inhibitors may be linked to the development of acute AD ( Oshima et al, 2017 ; Ting and Lo, 2021 ). Similarly, the Rap1 signaling pathway is associated with cell migration, polarization, and proliferation ( Cha et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The review of the literature identified seventeen eligible case reports with VEGFI related to AD (Aragon-Ching et al, 2008;Edeline et al, 2009;Carles, 2010;Formiga and Fanelli, 2014;Kurtz et al, 2014;Niwa et al, 2015;Koda et al, 2016;Hatem et al, 2017;Xu et al, 2017;Atsunori et al, 2018;Takada et al, 2018;Toru et al, 2018;Fubo and Gong, 2019;Zenoni et al, 2019;Jiang et al, 2020;Nikai et al, 2020;Ting and Lo, 2021). Thirteen of the seventeen patients are male, and four patients are female.…”
Section: Case Reports Collectionmentioning
confidence: 99%